Dry eye disease treatment improves subjective quality-of-life responses in patients with AMD, independent of disease stage - Nehal Nailesh Mehta; Ines D. Nagel; Akshay Agnihotri; Anna Heinke; Lingyun Cheng; Dirk-Uwe Bartsch; William R. Freeman; Maria-Laura Gomez (PLoS ONE, 2025)
Purpose To determine the impact of severity of age-related macular degeneration (AMD) on subjective treatment response in patients treated for dry eye disease. Methods A total of 203 eyes diagnosed with evaporative dry eye disease (DED) due to meibomian gland dysfunction were treated using the LipiFlow or MiBoFlo systems. From this cohort, 40 eyes with stable dry AMD (early, intermediate, or late stages) were included. Each participant completed the Ocular Surface Disease Index (OSDI) and Standard Patient Evaluation of Eye Dryness Questionnaire (SPEED) before treatment and at a 6-month follow-up. Changes in questionnaire scores were analyzed using one-way analysis of variance (ANOVA) to assess differences between AMD severity groups. Results Improvement in SPEED and OSDI scores, including vision related OSDI scores were observed across all AMD stages, with no significant differences between groups (p<0.05). Conclusion Managing DED improved quality of life (QOL) in patients with AMD, regardless of retinal disease severity. This highlights the importance of treating coexisting ocular surface conditions to enhance patient outcomes, even in the presence of significant maculopathy.